A Research on Consecutive User Experience Factors in the Reservation System of Home Sharing Platform - Ae Lee, Jung; Wook Park, Hyeon (International Journal of Engineering and Technology, 2018)
Background/Objectives: Currently, the global trend is leaning toward an age where individualsâ€™ experience is more importantly considered than individualsâ€™ possession.The purpose of this research is to systematically analyze the reservation stage of sharing economy platform in the perspective of consecutive user experiences.Methods/Statistical analysis: In this research, user experience factors indicated in the reservation stage of accommodation were deducted as properties of the six stages: search, booking request, booking confirmation, invoice, payment and voucher issuance. In addition such factors were analyzed as properties of user experiences consecutively and particularly indicated in home sharing platform included in sharing economy. Home sharing platform reservation system is particular in that it allows users to not only use its function to make reservations, but also experience rational benefits and emotional benefits in each stage. AirBnB(http://www.airbnb.co.kr) and Hanintel(http://www.hanintel.com) serving as representative services in home sharing platform were selected as the subjects, and their screen information displayed in the process of making individual reservations based on the searched regional accommodation data was collected and analyzed. Data was collected from 1st November 2016 to 18th December 2016.Findings: As a result of conducting an analysis, it was found that Hanintel focused on operating local affiliate programs allowing reservations as well as on its original role to make reservation and AirBnB promoting branding which emphasizes experience to be acquired by tourists have mutually different marketing strategies. In addition, it was also found that Hanintel was designed mainly based on reservation functions in the reservation stage whereas AirBnB was designed mainly based on emotion and participation in the reservation stage.Improvements/Applications: Considering that providers and consumers can share their resources and create new values through reliability in sharing economy based on ICT and cooperation consumption, the values and benefits of using home sharing platform can be promoted when the reservation system are designed to positively develop consecutive user experience in making reservations based on the premise that the functional usability is secured.Â